Political Literacy Based on Nahdlatul Ulama Community Civics in Strengthening Civic Virtue and Democracy - Zindan Baynal Hubi; Karim Suryadi; Endang Danial; Asep Mahpudz; Anwar Hidayat (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
The purpose of this study is to analyze the normative basis for fostering political literacy among Nahdliyin citizens and bahtsul masa’il as a framework for political education in the Nahdlatul Ulama tradition. This study employed a qualitative approach, utilizing a case study design. The results of the study indicate that the development of political literacy among Nahdliyin citizens is based on classical texts, the opinions of scholars, the decisions of the Nahdlatul Ulama Muktamar, and the outcomes of the Musyawarah Alim Ulama. The values instilled in the process of developing political literacy among Nahdliyin citizens can be categorized into four key areas, namely tasamuh, tawasuth, tawazun, and ta'adul. Political literacy development within Nahdlatul Ulama is centered on the lajnah bahtsul masa'il as a forum that examines various social, political, and religious issues in depth from the perspective of ahlussunnah wal jama'ah scholarship and theology. The lajnah bahtsul masa'il functions as a center for law enforcement and collective decision-making among scholars, Syuriah, Khatib, A'wan, and Tanfidziyah.